Enhancing Power Module Lifespan Through Power Distribution Approaches in a Three-Phase Interleaved DC/DC Converter - Rok Tavcar; Gabriela Maria Bordignon; Raul Santiago Munoz-Aguilar; Peter Zajec (IEEE Access, 2023)
This paper comprehensively analyzes various power distribution approaches to balance the stress on power modules (PM) in a three-phase interleaved DC/DC converter and increase its lifespan. Two implementations of power distribution are investigated: a symmetrical approach, where the PM utilizations are balanced by controlling the duration of their active intervals, and an asymmetrical approach, achieved by adjusting their reference currents. Regardless of the power distribution method, the estimation of accumulated PM stress is evaluated using two utilization metrics: energy-related and current-related. Different utilization and distribution control algorithms are validated using a hardware-in-the-loop (HiL) simulation setup, considering varying load profiles. The additional control modules require only minor modifications to the conventional two-loop controller structure, exhibit consistent responses, and steadily reduce the balance mismatch for all control combinations. The results demonstrate that asymmetrical control combined with energy utilization estimation yields the most favorable balance mismatch rate. Moreover, this methodology demonstrates superior energy efficiency in intervals characterized by balance mismatch, though it necessitates a significant initial labor investment for constructing the thermal mode.